Role of androgen receptor signaling in chemoresistance in urothelial cancer: a narrative review - Akai, Taro; Yamamichi, Gaku; Miyamoto, Hiroshi (Chinese Clinical Oncology, 2026)
Intravesical instillation of chemotherapeutic drugs remains a cornerstone in the management of non-muscle-invasive bladder tumor following transurethral surgery, where they are routinely employed to prevent disease recurrence and progression. In patients with locally advanced or metastatic urothelial carcinoma, cisplatin-based combination chemotherapy continues to represent the standard systemic treatment and has also been used in the neoadjuvant setting prior to radical cystectomy. Despite these established strategies, a substantial proportion of these patients exhibit intrinsic or acquired resistance to chemotherapeutic regimens, ultimately leading to poor oncologic outcomes, although the molecular mechanisms underlying chemoresistance remain only partially understood. Meanwhile, accumulating evidence has increasingly suggested a critical role of androgen receptor (AR) signaling in promoting not only the development and progression of urothelial cancer but also resistance to conventional non-surgical therapy for bladder cancer. In this review article, we aim to summarize available data suggesting that AR is involved in chemosensitivity in urothelial cancer.